Curcumin improves asthenozoospermia by inhibiting reactive oxygen species reproduction through nuclear factor erythroid 2‐related factor 2 activation. (3rd December 2019) - Zhou, Qiao; Wu, Xun; Liu, Yingmin; Wang, Xin; Ling, Xiufeng; Ge, Hongshan; Zhang, Junqiang
Abstract: We conducted this study for the purpose of evaluating the protective mechanisms of curcumin against oxidative stress in asthenozoospermic individuals. Asthenozoospermic individuals were grouped into AS group, curcumin treatment group and brusatol + curcumin treatment group. The sperm motility was measured by computer‐aided sperm analysis. We conducted flow cytometry and spectrophotometry to assess the levels of reactive oxygen species (ROS) and malondialdehyde (MDA). Chlortetracycline (CTC) was used to examine the acrosomal reaction of spermatozoa. Also, Western blotting was carried to measure antioxidant gene Nrf2 (nuclear factor erythroid 2‑related factor) expression level. As our results shown, treatment with curcumin significantly decreased ROS formation and MDA production, compared with spermatozoa of AS group; however, Nrf2 inhibitor, Brusatol, inhibited Nrf2 expression and sperm function. Our results have shown that curcumin might protect spermatozoa by regulating Nrf2 level.